PERAN LITERASI KEUANGAN DALAM PENGELOLAAN KEUANGAN MAHASISWA STIE PEMBANGUNAN TANJUNGPINANG - Siti Melisa; Salihi Salihi; Vanisa Meifari (Juremi: Jurnal Riset Ekonomi, 2023)
The purpose of study is to determine the role of financial literacy in student financial management, namely at the stage of determining the source of funds, using funds, risk management and future planning. This type of research is qualitative descriptive research, the object of this research is STIE Pembangunan Tanjungpinang, In this study using Primary data and Secondary data. The informants in this study are those who are in accordance with the identification of the problem, namely students of STIE Pembangunan Tanjungpinang semester 4, 6 and 8 who were selected by purposive sampling or deliberately in accordance with the criteria determined by the author.The result of study is the role of financial literacy at the stage of determining the source of funds, namely students are able to determine the source of funds based on the income obtained, the needs they have and the evaluation of expenses. The role of financial literation at the stage of using funds is that students are able to distinguish which needs and which are desires and never experience financial problems such as lack of funds. The role of financial literation at the risk management stage is to be able to make students have reserve funds for unexpected events or needs by saving. The role of financial literation at the future planning stage is that students are able to plan their future by following gold savings and have an idea of how to plan finances and businesses that want to be opened in the future.